Students' Mathematical Literacy in Addressing Contextual Questions Through Adversity Quotient - Puspita, Wita Ratna; Herman, Tatang; Dahlan, Jarnawi Afgani (Mosharafa: Jurnal Pendidikan Matematika, 2023)
Perolehan kemahiran matematika melibatkan kompetensi numerik dan penerapan konsep matematika untuk mengatasi tantangan dunia nyata. Penelitian ini bertujuan untuk menjelaskan literasi matematis siswa SMP dalam menyelesaikan permasalahan kontekstual, mengelompokkannya berdasarkan tingkat Adversity Quotient (AQ) yaitu climbingers, campers, dan quitters. Dengan menggunakan desain penelitian deskriptif dengan pendekatan kualitatif, penelitian ini difokuskan pada siswa Kelas VIII SMP N 32 Bandung. Pemilihan subjek penelitian bergantung pada tipe AQ ​​mereka. Pengumpulan data menggunakan lembar Adversity Response Profile (ARP), yang dilengkapi dengan pertanyaan esai dan wawancara. Analisisnya meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Temuan ini mengungkapkan ciri-ciri khusus di antara kategori-kategori AQ: (1) Siswa tipe pendaki menunjukkan kemahiran dalam perumusan masalah, perancangan dan implementasi strategis, serta interpretasi, penerapan, dan evaluasi hasil perhitungan, disertai dengan penguatan atas jawaban mereka; (2) Siswa tipe camper menunjukkan kemahiran dalam merumuskan masalah, merancang dan menerapkan strategi solusi, namun gagal dalam menyajikan interpretasi alternatif; dan (3) Siswa tipe quitter kesulitan dalam mengidentifikasi dan merumuskan strategi pemecahan masalah, menunjukkan kurang presisi dalam perhitungan, sehingga menghasilkan hasil yang salah. The acquisition of mathematical proficiency involves numerical competence and the application of mathematical concepts to address real-world challenges. This study aims to elucidate the mathematical literacy of junior high school students in resolving contextual problems, categorizing them according to their Adversity Quotient (AQ) levels, namely climbers, campers, and quitters. Employing a descriptive research design with a qualitative approach, the investigation focuses on Class VIII students at SMP N 32 Bandung. The selection of research subjects is contingent upon their AQ types. Data collection utilizes an Adversity Response Profile (ARP) sheet, incorporating essay questions and interviews. The analysis involves data reduction, data presentation, and drawing conclusions. The findings reveal distinctive attributes among the AQ categories: (1) Climber-type students demonstrate adeptness in problem formulation, strategic design and implementation, as well as the interpretation, application, and evaluation of calculation outcomes, accompanied by reinforcement for their answers; (2) Camper-type students exhibit proficiency in formulating problems, designing and applying solution strategies, yet fall short in presenting alternative interpretations; and (3) Quitter-type students struggle in identifying and formulating problem-solving strategies, displaying less precision in calculations, resulting in incorrect outcomes.